KOHESI DAN KOHERENSI DALAM KARANGAN SISWA SMP NEGERI 2 PURWOSARI KABUPATEN BOJONEGORO - Prakosa Wisnu Yakti (EDU-KATA, 2014)
Language has some levels, starting from phonology to syntax. Now, linguists tried to enter the discourse as one level of language, arguing that communication is usually done by a series of sentences. The series of cohesive and coherent sentences called discourse. Minimum unit for discourse is a clause. Clause serves as a messenger. Clause has a structure that is composed by rules specific sequence patterns that are recognized by the speech community of language. Language has several levels, ranging from phonology to syntax. Now,linguists tried to enter the discourse, as one level of language, arguing that communication is usually done with a series of sentences. Series of cohesive and coherent sentences called discourse. Minimum unit for discourse is a clause. Clause serves as a messenger. Clause has a structure that is composed by rules specific sequence patterns that are recognized by the speech community of a language. Discourse is a group of sentences that have a unity of communicative information.This condition indicates that the perceived critical discourse analysis in communication. This assessment is not excessive, considering the man has always struggled with the discourse in his life. Every time human communicate with others. They communicate with each other in making discourse, which is a series of sentences that are cohesive and coherent.